Culturas e sistemas simbólicos: "meeting pot" na arte rupestre da Bahia - Silva, Joaquim Perfeito da (1998)
This thesis examines the results of stylistic analysis of 50 rock art sites in 26 municipalities in Bahia State, located mainly in high altitude areas of the Chapada Diamantina, Planalto de Conquista and Serra Geral da Bahia and comprising a total of approximately 1.800 square meters of painted area in caves, rock shelters and canyons. In analysing and classifying the sites, we opted to organize an empirical corpus of typical signings taken from the group of sites and coded so as to be able to apply mathematical and statistical methods. This methodological procedure is able to reveal logical patterns of dispersion and contextualized signs, where chance becomes improbable and the signs take on the status of symbols defining distinct cultural horizons. In this way, contrasted and contextualized in styles and traditions, the signings lead one to see rock art as a way of "saying something about" or "wanting to show that"; that is, as a study that penetrates the field of non-verbal signs, of symbols that doubtless conceal a certain organized view of the world.